Pengembangan Instrumen Tes Berbasis Literasi Kimia pada Materi Struktur Atom dan Nanoteknologi Kurikulum Merdeka Fase E SMA - Dorisya Putri, Salsya Awra; Yusmaita, Eka (Universitas Negeri Padang, 2024)
Chemical literacy is one of the literacies that needs to be developed for students due to the proximity of chemistry to everyday life and the community environment. Indonesia's literacy skills are still relatively low because they are categorized as countries with scores below the average, this is evidenced by the results of PISA. The low literacy skills are caused by several factors such as the difficulty of understanding concepts where learning is not associated with events that occur in everyday life. So that students become not literate in chemical literacy. Therefore, the importance of efforts to build students' chemical understanding skills as a whole through the development of chemical literacy-based test instruments on atomic structure and nanotechnology materials. This research is a Research and Development (R&D) study using the Rasch Model through 10 steps by Xiufeng in 2020. The resulting test instrument is expected to be able to measure students' chemical literacy skills on atomic structure and nanotechnology materials. Content validity analysis by validators found that all items were in the valid category. Reliability analysis obtained a person reliability value of 0.96 and the aspect reliability value was 0.93.